Administrative platform for online tutoring by using ruby on rails / Muhammad Aris Adham Misri - Misri, Muhammad Aris Adham (2019)
Within this current era and technologies, looking for advertisement when in look for a tutor seem too much of a nuisances. Not just that, it is also harder for the tutor to look for student when they only relying on flyers and pamphlet. Research/study material also hard to retrieve and cost a lot. Besides that, the use of physical book seem outdated and physically burdening. The purpose of the project is to provide a platform where it's easier for student and tutor to assign with each other. Other than that, the platform also provide research and study material in form of electronic file/document like the .pdf, .doc and .ppt .The project will be builds as web application so that it will be easier for user to access into it whether by computer or mobile. Ruby on Rails will be used to develop the web application for online tutoring. It is because Rails is good for rapid application development (RAD), as the framework makes it easy to accommodate changes. Last but not least, the project is intended to make it easier for user to pursue knowledge via online tutoring.